The outcome of possible events following the hospital discharge of patients with HFmrEF after MI as compared with those with HFmrEF without MI: a propensity score matching analysis - Liu, Zhican; Zhang, Lingling; Zeng, Jianping; Jiang, Mingyan (Frontiers in Cardiovascular Medicine, 2025)
BackgroundClinical studies on heart failure (HF) with mildly reduced left ventricular ejection fraction (HFmrEF) are gradually increasing. However, relatively few studies have examined patients with HFmrEF after myocardial infarction (MI), and the prognosis of such patients remains unclear. Therefore, we conducted a retrospective evaluation of HFmrEF patients with/without MI using a propensity score matching analysis (PSMA).MethodsA total of 1,691 patients with HFmrEF were included in this study. Of these patients, 873 had a diagnosis of MI, and 818 did not. After propensity score matching, we used Kaplan–Meier analysis and Cox regression to compare all-cause mortality, cardiovascular death, or HF readmission (CV events).ResultsAfter the first PSMA, the MI group had a lower risk of all-cause mortality [hazard ratio (HR) 0.6; 95% confidence interval (95% CI) 0.5–0.8] compared with the non-MI group; however, there was no significant difference in the incidence of CV events (HR 0.9; 95% CI 0.7–1.2). After the second PSMA, which additionally matched for PCI performance in the MI group, there were no differences in the risk of all-cause mortality (HR 1.0; 95% CI 0.7–1.5) or CV events (HR 1.1; 95% CI 0.8–1.5) between the MI and non-MI groups.ConclusionsThere was no difference in all-cause mortality and CV events between patients with HFmrEF with and without MI. However, among patients with HFmrEF and MI, those who underwent PCI had a much lower risk of all-cause mortality compared with patients with HFmrEF without MI and those with HFmrEF after MI who did not undergo PCI.